Que ciência da informação precisamos para enfrentar a complexidade? = What information science we need to meet complexity? - Silva, Armando Malheiro da (2016)
A scientific meeting with tradition and consistency like this that brings us together has supported especially by those who have dedicated work and enthusiasm for teaching and research in Information Science, it is imperative to reflect on the challenges facing this course in itself complex, in front of an overall framework of maximum complexity. A discipline that lack consensus among its practitioners and learners about the natural matrix - interdisciplinary or trans and interdisciplinary ?- and the more general field of integration - Social Sciences or Information and Communication Technologies? Given that there is a serious epistemological debate deficit that ENANCIB have served to fill, although there is a need and room for more. It is intended here to discuss the internal, external and training plan of the CI the ways that it is urgent to draw and make a was challenging as the one we are experiencing, starting from recent milestones published to signal the state of discipline in certain socio-cultural landscapes, particularly the Anglo-American and Nordic-Germanic. The call to reflection and constructive debate, if heeded is a precious and worth gain, so that we contribute to it.